2023
DOI: 10.1002/pro.4656
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of Hsp90 dependence of Src kinase revealed by deep mutational scanning

Abstract: Hsp90 is a molecular chaperone involved in the refolding and activation of numerous protein substrates referred to as clients. While the molecular determinants of Hsp90 client specificity are poorly understood and limited to a handful of client proteins, strong clients are thought to be destabilized and conformationally extended. Here, we measured the phosphotransferase activity of 3929 variants of the tyrosine kinase Src in both the presence and absence of an Hsp90 inhibitor. We identified 84 previously unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…HSF1 is a transcription factor that can induce the expression of HSPs (Kurop et al, 2021). Under non-stress conditions, HSF1 exists in an inactive monomer form and forms a complex with HSP90 (Nguyen et al, 2023). Studies found that the heat shock response (HSR) is regulated by the phosphorylation of HSF1 and the dissociation of HSP90 (Gong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…HSF1 is a transcription factor that can induce the expression of HSPs (Kurop et al, 2021). Under non-stress conditions, HSF1 exists in an inactive monomer form and forms a complex with HSP90 (Nguyen et al, 2023). Studies found that the heat shock response (HSR) is regulated by the phosphorylation of HSF1 and the dissociation of HSP90 (Gong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%